Prognostic value of elevated copeptin and high-sensitivity cardiac troponin T in patients with and without acute coronary syndrome: the ConTrACS study - Waldsperger, Hanna; Biener, Moritz; Stoyanov, Kiril M.; Vafaie, Mehrshad; Katus, Hugo; Giannitsis, Evangelos; Müller-Hennessen, Matthias (Journal of Clinical Medicine, 2020)
Aims: We aimed to assess the prognostic role of copeptin in patients presenting to the emergency department with acute symptoms and increased high-sensitivity cardiac troponin T. Methods: A total of 3890 patients presenting with acute symptoms to the emergency department of Heidelberg University Hospital were assessed for increased hs-cTnT (>14 ng/L) from three cohorts: the Heidelberg Acute Coronary Syndrome (ACS) Registry (n = 2477), the BIOPS Registry (n = 320), and the ACS OMICS Registry (n = 1093). In a pooled analysis, 1956 patients remained, comprising of 1600 patients with ACS and 356 patients with non-ACS. Results: Median follow-up was 1468 days in the ACS cohort and 709 days in the non-ACS cohort. Elevated copeptin levels (>10 pmol/L) were found in 1174 patients (60.0%) in the entire cohort (58.1% in ACS and 68.5% in non-ACS, respectively) and mortality rates were significantly higher than in patients with normal copeptin levels (29.0% vs. 10.7%, p < 0.001). In a multivariate Cox regression, elevated copeptin was independently associated with all-cause death in the ACS (HR = 1.7, 1.3–2.3, p = 0.002) and non-ACS cohort (HR = 2.7, 1.4–5.0, p = 0.0018). Conclusion: Copeptin may aid in identifying patients at risk for adverse outcomes in patients with increased levels of hs-cTnT in ACS patients and in non-ACS conditions.